INOVASI KURIKULUM DALAM PEMBELAJARAN AGAMA ISLAM - Nafiatul Nafiatul Faizah; Setyo Supratno (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
Curriculum innovation in Islamic Religious Education (IRE) learning is a strategic effort to improve the quality of education in order to remain relevant to the development of the times, the needs of learners, and global challenges. The IRE curriculum is not only oriented toward mastery of religious content, but also toward character building, the development of moderate attitudes, and critical thinking skills. This study aims to examine the concept, forms, and urgency of curriculum innovation in IRE learning. The method used is library research by analyzing various sources such as books, scientific journals, and relevant curriculum documents. The results indicate that curriculum innovation in IRE can be implemented through the development of learning objectives, the integration of Islamic values with science and technology, the application of active and contextual learning methods, and the use of varied and digitally based learning media. These innovations are expected to create an effective, engaging, and meaningful IRE learning process, thereby shaping learners who are faithful, have noble character, and are capable of facing the dynamics of modern life. Keywords: curriculum innovation, learning, Islamic Religious Education